A Community of Inquiry lens into nursing education: The educators' experiences and perspectives from three Australian universities. (July 2021) - Smadi, Omar; Chamberlain, Diane; Shifaza, Fathimath; Hamiduzzaman, Mohammad
Abstract: Aim: Nursing is a social and collaborative profession; therefore, nursing education requires a pedagogy that supports the establishment of a collaborative learning community. Despite the limited use of the Community of Inquiry framework in Australian nursing courses, the educators viewed it as applicable for course design. This paper aims to understand Australian nurse educators' current practices in designing and delivering courses using the Community of Inquiry lens. Design and methods: This paper represent the second phase of the explanatory mixed-methods approach—the data collected in October 2019 via semi-structured interviews with eleven nurse academics from 3 Australian universities. Results: the deductive thematic analysis using the Community of Inquiry coding template confirmed that the 'cognitive presence' and its indicators are implicitly embedded in online/blended courses. But the 'social presence' and 'teaching presence' are faced with some challenges: the underuse of discussion forums by students, the use of social media pages with exclusion of educators and the educators' role of content development rather than course design. Conclusions: The study findings suggest that the Community of Inquiry framework's explicit application would strengthen 'social and teaching' presences in nursing courses design. Further studies on nursing students' evaluation and perspectives about courses design regarding Community of Inquiry are essential.